The type of visual biofeedback influences maximal handgrip strength and activation strategies - Marcel-Millet, P., Gimenez, P.; Groslambert, A.; Ravier, G.; Grospretre, S. (European Journal of Applied Physiology, 2021)
Purpose: This study investigated the effects of force and electromyographic (EMG) feedbacks on forearm muscle activations and handgrip maximal isometric voluntary contraction (MIVC). Methods: Sixteen males performed a set of MIVC in four different feedback conditions: (1) NO-FB: no feedback is given to the participant; (2) FORCE-FB: participants received a visual feedback of the produced force; (3) AGO-FB: participants received a visual feedback of the EMG activity of two agonist grip muscles; (4) ANTAGO-FB: participants received a visual feedback of the EMG activity of two hand extensors muscles. Each feedback was displayed by monitoring the signal of either force or electrical activity of the corresponding muscles. Result: Compared to NO-FB, FORCE-FB was associated with a higher MIVC force (+ 11%, P < 0.05), a higher EMG activity of agonist and antagonist muscles (+ 8.7% and + 9.2%, respectively, P < 0.05) and a better MIVC/EMG ratio with the agonist muscles (P < 0.05). AGO-FB was associated with a higher EMG activity of agonist muscles (P < 0.05) and ANTAGO-FB was associated with a higher EMG activity of antagonist muscles (P < 0.05). MIVC force was higher in the agonist feedback condition than in the antagonist feedback condition (+ 5.9%, P < 0.05). Conclusion: Our results showed that the MIVC force can be influenced by different visuals feedback, such as force or EMG feedbacks. Moreover, these results suggested that the type of feedback employed could modify the EMG-to-force relationships. Finally, EMG biofeedback could represent an interesting tool to optimize motor strategies. But in the purpose of performing the highest strength independently of the strategy, the force feedback should be recommended.